Temperature-Driven Growth Variation in a Deep-Sea Fish: The Case of Pagellus bogaraveo (Brünnich, 1768) in the Azores Archipelago - Neves, João; Giacomello, Eva; Menezes, Gui M.; Fontes, Jorge; Tanner, Susanne E. (Frontiers in Marine Science, 2021)
The deep ocean ecosystem hosts high biodiversity and plays a critical role for humans through the ecosystem services it provides, such as fisheries and climate regulation. However, high longevity, late reproduction, and low fecundity of many organisms living in the deep ocean make them particularly vulnerable to fishing and climate change. A better understanding of how exploitation and changing environmental conditions affect life-history parameters (e.g., growth) of commercially important fish species is crucial for their long-term sustainable management. To this end, we used otolith increment widths and a mixed-effects modeling approach to develop a 42-year growth chronology (1975–2016) of the commercially important deep-sea fish species blackspot seabream (Pagellus bogaraveo) among the three island groups of the Azores archipelago (Northeast Atlantic). Growth was related to intrinsic (age and age-at-capture) and extrinsic factors (capture location, temperature-at-depth, North Atlantic Oscillation (NAO), Eastern Atlantic Pattern (EAP), and proxy for exploitation (landings)). Over the four decades analyzed, annual growth patterns varied among the three island groups. Overall, temperature-at-depth was the best predictor of growth, with warmer water associated with slower growth, likely reflecting physiological conditions and food availability. Average population growth response to temperature was separated into among-individual variation and within-individual variation. The significant among-individual growth response to temperature was likely related to different individual-specific past experiences. Our results suggested that rising ocean temperature may have important repercussions on growth, and consequently on blackspot seabream fishery production. Identifying drivers of blackspot seabream growth variation can improve our understanding of past and present condition of the populations toward the sustainable management of the fishery.